Analisis Sifat Mekanik Hasil Pengelasan SMAW dengan Akar Las Tig dan Las SMAW pada Pipa API 5L - Muas M; Muhammad Arsyad Suyuti; Rasul Rasul; Patta Hajji (Politeknik Negeri Ujung Pandang, 2019)
The purpose of this research is to know the mechanical properties of the welds due to the current variation of welding joint API 5L using TIG and SMAW welding root methods. Preparation of specimens of pipe API 5L PSL1 grade X56 (Ø 177.8 mm, length 200 mm, width 7 mm), then specimens preparation were made in a single V 600, root gap 2mm, root face 2mm. Filling the welding roots with TIG welding and SMAW using electrodes E7018 with a current variation 70A, 80A, 90A. Mechanical tests consist of tensile, bending and hard test. The results showed that the quality of a good TIG root weld at 70A, the highest tensile strength of the weld joint 52.27 kgf/mm2 (70A), the highest hardnest 164,217 HRB (90A), the bending strength 1.123,061 N/mm2 (70A) using face bend method and 1,172,959 N/mm2 with root bend. In SMAW root welding, the highest tensile strength 54.27 kgf/mm2 (70 A) , the highest hardnest 158.717 HRB (70 A), the highest bending strength 1.115,611 N/mm2 (70 A) using face bend method, and 1.161,748 N/ mm2 with root bend.